MENGGAGAS MODEL PENGINJILAN GEREJA RASULI SEBAGAI SOLUSI PERTUMBUHAN GEREJA MASA KINI - wijayanto, wahyudi sri; Herika, Herika (Shift Key : Jurnal Teologi dan Pelayanan, 2023)
The model of the apostolic church is a church that shows the growth of the church in quantity and quality. One of the hallmarks of the apostolic church was the evangelistic movement at that time. This study aims to discover how the apostolic church model can be applied today. This research uses a qualitative method with the type of literature study research or document study. The results of this study are education on the importance of evangelism for the church, the church growth ministry today and the apostolic church model as a solution. Keywords: Evangelism, Church Growth, Apostolic